2022
DOI: 10.3389/fpsyt.2022.913821
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep Quality and Factors Among Reproductive-Age Women in Southwest Ethiopia

Abstract: BackgroundAdequate sleep is vital for physical and mental wellbeing. Sleep-related problems including poor quality of sleep have been increasing throughout the world among reproductive-aged women. Poor sleep quality has been related with number of diseases and health problems However, evidences are scarce regarding poor sleep quality and its associated factors among women of the reproductive age group in Ethiopia.ObjectiveTo assess sleep quality and associated factors among women of reproductive age group in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…This finding aligns with that of another study on a Chinese adult population (Madrid-Valero et al, 2017). A possible explanation for this is hormonal factors, such as premenstrual syndrome and menstrual pain (Bogale et al, 2022). Another study stated that a possible explanation is higher psychological and behavioral in females, such as greater insomnia and depression with lower sleep quality (Guadagni et al, 2020).…”
Section: Resultssupporting
confidence: 87%
“…This finding aligns with that of another study on a Chinese adult population (Madrid-Valero et al, 2017). A possible explanation for this is hormonal factors, such as premenstrual syndrome and menstrual pain (Bogale et al, 2022). Another study stated that a possible explanation is higher psychological and behavioral in females, such as greater insomnia and depression with lower sleep quality (Guadagni et al, 2020).…”
Section: Resultssupporting
confidence: 87%
“…In this systematic review and meta-analysis, we included nine cross sectional studies ( Amare, Chekol & Aemro, 2022 ; Anbesaw et al., 2021a ; Anbesaw et al., 2021b ; Bogale et al, 2022 ; Dule et al, 2021 ; Jemere et al, 2021 ; Belete et al., 2021 ; Molla, Nigussie & Girma, 2022 ; Takelle, Muluneh & Biresaw, 2022 ; Anbesaw et al., 2021b ) on the prevalence and associated factors of poor sleep quality and suicidal ideation among pregnant women during the COVID-19 pandemic in Ethiopia. Based on the types of mental disorders; six studies ( Amare, Chekol & Aemro, 2022 ; Bogale et al, 2022 ; Anbesaw et al., 2021a ; Anbesaw et al., 2021b ; Jemere et al, 2021 ; Takelle, Muluneh & Biresaw, 2022 ; Dule et al, 2021 ) were reported about poor sleep quality; three studies ( Belete et al., 2021 ; Anbesaw et al., 2021b ; Molla, Nigussie & Girma, 2022 ) were reported about suicidal ideation. Furthermore, the summarized data of the key characteristics of the included studies for this review were showed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We considered moderate quality, and high-quality studies for this review. Thus, one study ( Dule et al, 2021 ) that was appraised as moderate quality and eight studies ( Amare, Chekol & Aemro, 2022 ; Bogale et al, 2022 ; Anbesaw et al., 2021b ; Belete et al., 2021 ; Jemere et al, 2021 ; Molla, Nigussie & Girma, 2022 ; Takelle, Muluneh & Biresaw, 2022 ) that were appraised as high quality were considered for final systematic review and meta analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations